Association between Women’s Empowerment and Other Socio-Demographic and Nutritional Factors on Stunting among Children Aged 6 to 59 Months: Data from 2016 EDHS - Baruda, Yirgalem Shibiru; Yilma, Mengistu; Gebremariam, Mulugeta Betre; Assebe, Lelisa Fekadu (Journal of Maternal and Child Health, 2022)
Background: Stunting is the most prevalent form of malnutrition in children under five years of age in Ethiopia. Evidence supporting women’s impact on reducing child stunting is limited. In this paper, we examine the association between women’s empowerment and socio-demographic factors on stunting among children aged 6 to 59 months. Subjects and Method: The study used the EDHS 2016 dataset. Children aged 6-59 months whose mothers (aged 15-49 years) were living with their husbands at the time of the survey were included. We enrolled 8,496 mother and child pairs. Complex sample logistic regression analysis was employed to determine the association between child stunting and the predictors. Data analyses were employed using SPSS Version 22. Results: Around 2,624 (31%) of the mothers were 25 to 29 years old. In the 12 months before the survey, around 45% (3,806) of the mothers were employed; 2,072 (54%) of them had seasonal jobs, and the 1,734 (45%) remaining mothers had full-time employment. Among employed mothers, about 50.5% (1,921) had not received payment for their work. Household wealth index (AOR= 1.9; 95% CI= 1.44 to 2.73) and maternal height (AOR= 1.9; 95% CI= 1.28 to 2.82), and having a boy child (AOR= 1.3; 95%CI= 1.08 to 1.46) is more liked associating with stunting. But maternal attitude towards wife-beating (AOR= 1.1; 95% CI= 0.89 to 1.26) had no association with it. Conclusion: children born from the poorest households, low maternal height (<145cm), and male sex have increased risk of stunting. Lastly, Mothers' economic and socio-familial empowerment do not predict the risk of child stunting.  Keywords: stunting, empowerment, women, Ethiopian demographic health survey. Correspondence: Yirgalem Shibiru Baruda. School of Public Health, Addis Ababa University, Addis Ababa, Ethiopia. Email: yirgalemsh75@gmail.com.